Development Taman Surya Nusantara to increase new and renewable energy in Indonesia - Ananda Dwi Kartika; Rodrikson Alpian Medlimo (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: The aim of this research is to achieve sustainable development by reorienting the use of energy from fossil energy to new and renewable energy through the massive and consistent use of solar energy in Indonesia. Research Methodology:  This study employed a normative empirical method with a descriptive analysis approach. Secondary data were acquired through meticulous literature review and subjected to qualitative analysis. The outcomes of the analysis serve as the cornerstone for accurate conclusions within the research (Soerjono & Mamudji, 2007). Results: The research results show that the development of Taman Surya Nusantara is instrumental, extensive, and comprehensive, to be carried out as a key to facing the challenges of the global energy crisis, as well as a strategic step to achieve sustainable development goals in Indonesia. Limitations: The construction of Taman Surya Nusantara will receive a positive response from all parties, with an orientation towards achieving the ideal use of solar energy for the realization of sustainable development. Contributions: This research explains that developments in science and technology are signs of the need for reformulation of the use of solar energy in Indonesia. In such conditions, it has implications for the phenomenon of "sustainable development goals," meaning that the dimensions of life are required to be adaptive to conditions of sustainable development in line with the essence of welcoming Golden Indonesia 2045.